Upitnik za procenu farmakoterapijske pismenosti roditelja predškolske dece u Srbiji: konstrukcija i psihometrijske karakteristike - Ubavic, Stana; Krajnović, Dušanka; Bogavac, Nataša (Vojnosanitetski pregled, 2021)
Background/Aim. Valid and reliable instruments were emphasized in studies of pharmacotherapy literacy which is “the capacity to obtain, evaluate, calculate, and comprehend basic information about pharmacotherapy and actions necessary to make appropriate medication-related decisions”. The aims of this study were: to develop an instrument for assessment of pharmacotherapy literacy among parents of pre-school children in Serbia (PTHL-SR) and to evaluate psychometric properties. Methods. This study was a four – stage methodological one, conducted from November 2015 to October 2016. Instrument content was established through qualitative and quantitative expert reviews in the first and second phase. Experts had to answer about clarity and relevance of questions. Content Validity Ratio (CVR) was calculated based on the necessity and relevance of questions. Third phase was pre-testing of initial instrument to assess comprehensibility of questions. In the fourth phase, 100 parents completed questionnaire at several kindergartens in Belgrade, to determine questionnaire’s reliability through internal and external consistency, using Cronbach’s alpha coefficient and correlation between classes. Results. The 16-items questionnaire was developed (initial PTHL-SR) and pre-tested on a pilot sample of 20 parents. It had 4 groups of questions about knowledge, understanding, numerical skills and access to medicines – related information. Psychometric properties of questionnaire were tested on 100 parents, mostly women (78%), aged 30 – 40 years (81%), with two children (62%). Content Validity Ratio (CVR =0.875) was significant and adequate (Lawshe CVR8=0.780). Reliability was demonstrated by ICC = 0.934; satisfactory internal consistency was demonstrated with Cronbach’s alpha of 0.939 (0.815-0.979). Conclusion. PTHL-SR is reliable instrument for assessment of pharmacotherapy literacy among parents of pre-school children in Serbia and can be used for evaluation of understanding, calculating and accessing medicines-related information. Key words: pharmacotherapy, health literacy, parents, questionnaire